Key influential factors for sludge pre-fermentation process design--a case study - Chen, W (Environmental technology, 2004)
Sewage sludge pre-fermentation process produces readily biodegradable carbon, which is essential for reliable biological phosphorus removal and efficient denitrification. This bench scale study was to develop site-specific design parameters for a sludge fermentation process, and to look into the effects of various influential factors. The key factors investigated induded solids retention time (4-8 days), temperature (9-19 degrees C) and sludge concentrations (0.5%-4% DS). The optimum Volatile Fatty Adds yield was found at a sludge concentration of 1%-1.5% DS. A solid retention time of 4 days at 15-20 degrees C was found to be most cost effective. The fermentation reaction was temperature sensitive, which was found to be inefficient at temperature below 12-15 degrees C. Under the optimum conditions, 80-100 mgVFA g(-1) VSS can be generated from fermentation process, which will result in an increase of 20-24 mg l(-1) in the settled sewage based on average flow. A significant pathogen reduction level was also demonstrated over the fermentation period. Liquid sludge from the small rural wastewater treatment plants is often imported to a regional sludge treatment centre for more advanced treatment to comply with the Regulations. The suitability of this imported sludge for pre-fermentation process was also investigated in this study